Volumetric Behavior of Sodium Saccharin in Water and (0.1, 0.3, and 0.5) m Fructose at (298.15, 303.15, 308.15, and 313.15) K - Kharat, Sanjeevan J.; Munde, Sachin M. (Orbital: The Electronic Journal of Chemistry, 2017)
In order to get the information regarding the sweetener-water and sweetener-sweetener interactions, densities of sodium saccharin in water and (0.1, 0.3, and 0.5) m fructose have been measured at (298.15, 303.15, 308.15, and 313.15) K by the use of bicapillary pycnometer. From density values, partial molar volumes, expansion coefficient, Hepler’s constant, apparent specific volumes, partial molar volumes of transfer, doublet and triplet interaction coefficients have been calculated. From density study, it has been concluded that strong water-sodium saccharin interactions exist. Sodium saccharin is water structure maker. Strong interactions exist between sodium saccharin and fructose. In presence of fructose, the interactions exist between hydrophilic group (–OH, C=O, and –O–) of fructose and sodium ion of sodium saccharin in aqueous solutions of sodium saccharin. All investigated solutions exhibit sweet taste. DOI: http://dx.doi.org/10.17807/orbital.v9i1.921